Pachyonychia congenita associated with granulosis rubra nasi. - Xu, B.; Zhang, R-Z.; Zhu, W-Y. (European Journal of Pediatric Dermatology, 2013)
Pachyonychia congenita (PC), a rare autosomal dominant keratin disorder caused by mutations in keratin genes KRT6A/B, KRT16 or KRT17, is characterized by painful plantar keratoderma and hypertrophic nail dystrophy. It usually begins within the first few months of life. We report a case of a 3-year-old boy born to unaffected parents. He presented with hypertrophic nail dystrophy and subungual hyperkeratosis of all 20 nails, verrucous hyperplasia on the left helix, hyperkeratotic plaques of palms and soles, follicular papules on the waist, knees and elbows, and oral leukokeratosis. The patient's clinical presentation and history were consistent with PC type 1. Moreover, the boy had granulosis rubra nasi, characterized by papular red lesions of the nose associated with hyperhidrosis and usually inherited as an autosomal dominant trait. The coexistence in the same patient of the two inherited skin disorders has not been so far reported.